2021
DOI: 10.1192/bjo.2021.1042
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of computerised positive mental imagery training as a treatment adjunct in in-patient mental health settings: randomised controlled trial

Abstract: Background Positive affect and anhedonia are important but challenging targets for mental health treatments. Previous research indicates the potential of a computerised cognitive training paradigm involving generation of positive mental imagery, termed positive mental imagery training (PMIT), to increase positive affect and reduce anhedonia. Aims Our main aim was to investigate the feasibility of PMIT as a positive affect-focused, transdiagnostic adjunct to treatment as usual for patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Supporting the cognitive reserve hypothesis, instructing participants to imagine a future event vividly led to a significant reduction in delay discounting, impulsive behavior and substance consumption ( Peters and Büchel, 2010 ; Forster et al, 2021 ). Similar effects have been found for internalizing behavior such as depression and anxiety ( Jing et al, 2016 ; Westermann et al, 2021 ).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Supporting the cognitive reserve hypothesis, instructing participants to imagine a future event vividly led to a significant reduction in delay discounting, impulsive behavior and substance consumption ( Peters and Büchel, 2010 ; Forster et al, 2021 ). Similar effects have been found for internalizing behavior such as depression and anxiety ( Jing et al, 2016 ; Westermann et al, 2021 ).…”
Section: Discussionsupporting
confidence: 76%
“…Experimental studies confirmed these findings and suggest that the observed link may provide possible implications for clinical practice (e.g., Renner et al, 2021 ). For example, training or instructing EFT about positive future events did not only elicit positive affect in the here-and-now, but also increased anticipated pleasure and the intention to perform related activities in healthy controls ( Hallford et al, 2020a ; Westermann et al, 2021 ; Hallford et al, 2022 ). Beyond EFT, there is some, albeit considerably less evidence, that also other facets of future-oriented cognition such as delay discounting, planning and prospective memory may be altered in subjects showing internalizing symptoms ( Miloyan et al, 2014 ; McFarland and Vasterling, 2018 ; for a review).…”
Section: Introductionmentioning
confidence: 97%
“…Holmes, Lang, and Shah, 2009 ) and clinical (e.g. Blackwell et al, 2015 ; Westermann et al, 2021 ) studies. The interventions comprised a series of training sessions (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…More recently applications have focused specifically on anhedonia (e.g. Blackwell et al, 2015 ; Westermann et al, 2021 ), a challenging clinical target where there is great need for treatment innovation (e.g. Craske, Meuret, Ritz, Treanor, and Dour, 2016 ; Dunn et al, 2020 ).…”
mentioning
confidence: 99%
“…Whitehead et al, 2016). As you will collect outcome data during a feasibility or pilot trial you will generate estimates of likely efficacy of your intervention (see Hitchcock et al, 2018; Kanstrup et al, 2021; Westermann et al, 2021, for some examples); if these provide absolutely no indication of likely success, you may wish to take a step back before moving to a full-scale RCT. However, effect size estimates generated from feasibility and pilot studies should be treated with a high level of caution, particularly given the a priori knowledge that the trial is underpowered.…”
Section: Should You Really Do a Clinical Trial?mentioning
confidence: 99%